REFLECTION OF MOTIVATION ON WORK PRODUCTIVITY IN INDONESIA (LITERATURE STUDY) - Sifra Aditha Mileniari; Khairul Ikhwan (Transpublika Publisher, 2022)
The goal of this study is to determine the evolution of work productivity research in Indonesia. This study sample consists of publications published in 15 reputable national journals between 2008 - 2019. The sample consists of 20 publications discussing work productivity. The technique employed is the field mapping technique proposed by (Hesford et al., 2007). This study categorizes papers according to their subjects, research methodologies, and research sectors. The findings suggest that the dependent variable with the most research is the work productivity variable, whereas the independent variable with the most research is the work motivation variable. Quantitative research methods are the most popular, and the majority of research is undertaken in the private sector.